DAMPAK FAKTOR INTERNAL DAN EKSTERNAL TERHADAP INDUSTRI KELAPA SAWIT INDONESIA : ANALISIS MODEL EKONOMETRIKA - Zainuddin Zainuddin (Universitas Batanghari Jambi, 2015)
Model systems of simultaneous equations were built to analyze the impact of several internal factors and external factors of the Indonesian palm oil industry. The scope of the study is a model of Indonesian palm oil commodity as well as various aspects related to the model. The data used is the annual time series from 1984 to 2012 were collected from various sources. Equation system model estimation method using two stage least squares (2SLS) with the help of SAS software.Results of the estimation model used has sought good enough to explain the empirical phenomena. This is because the models are built too small so that the necessary information through a variety of behavioral equations in the model fairly limited (not so powerful forecasting) so sometimes partly the result of historical simulation detrimental effect appropriate (opposite) with empirical facts.Of the various scenarios that do turns combination of increased export prices of cooking oil Indonesia accompanied by a decrease in real interest rates and rising real wages of industrial impact good enough for Indonesian palm oil industry such as the production and export of palm oil increased by relatively large, although berfek negatively affect oil exports Crude palm oil (CPO). It is actually very good for Indonesian export commodities shift to products with higher value added, and these conditions will encourage domestic industrialization of palm oil processing.Keyword : palm oil , production , export , internal and external factors , the econometric model .